Occurrence of Thrips palmi Karny (Thysanoptera thripidae) and its predator, Orius tantillus (Motschulsky) (Hemiptera:Anthocoridae) in the Philippines - Calilung, V. J.; Malabayabas-Arcelo, M.; Calilung, M. V. J. (1997)
Intermittent surveys conducted during a 3-year study of Thrips palmi Karny and its anthocorid predator, Orius tantillus (Motschulsky), showed that it still remains the most serious pest of watermelon and other fruit vegetables in the Philippines.

T. palmi is widely distributed and occurs on different plants throughout the year. Fifty-eight plant species were found to harbor T. palmi but some may not be true hosts. The weed host, Amaranthus spinosus L., harbors T. palmi as well as O. tantillus and two other thrips species, T. flavus Schrank and T. subnudula (Karny), during its flowering stage.

O. tantillus was consistently found in watermelon throughout the areas surveyed during the study. In addition to T. palmi, its prey range includes T. tabaci Lindeman, T. flavus Schrank, T. subnudula (Karny), Frankliniella intonsa Trybom, F. schultzei Trybom, F. williamsi Hood, Ceratothrips reticulatus Reyes, Exothrips sacchari (Moulton), and Bolacothrips graminis (Priesner). It was also observed to feed on other small insects, eggs and younger larvae of larger insects and other arthropods, such as mites.
Keywords: Agricultural pests; Insect migration